Circling a subject: chasing happiness in creative practice. Issue 1 (2nd January 2018) - Meekings, Sam
ABSTRACT: This paper will examine issues arising from the attempt to record and portray happiness in a narrative. Roland Barthes writes of the impossibility of writing definitively about this most subjective of emotions in The Pleasure of the Text, in which he asserts that a writer 'can only circle such a subject' (34). This paper will therefore examine some of the ways in which I circle around the subject in my own creative practice, and suggest some working definitions of 'textual' happiness that can inform the writing process. It will analyse different conceptions and depictions of happiness, including Pater's present tense epiphanies; depictions of states of transcendent joy; happiness as a facet of the past tense; and how Barthes' definition of the text of bliss might be embodied within a creative text. The paper will include several excerpts from my creative struggle with this emotion, and end with a demonstration of how happiness within a text often proves contradictory and unsettling.